A Glimpse into the Future of Quantum Computing and AI - Bayan, Fayyad Mohammed Hani (Journal of engineering sciences and information technology, 2024)
This research examines the transformative potential unlocked by the convergence of Quantum Computing and Artificial Intelligence, two pioneering technologies poised to drive unprecedented breakthroughs in fields such as healthcare, finance, and supply chain management. The integration of these technologies represents a gateway to a new era of innovation, surpassing the limitations of traditional systems. This fusion delivers unmatched speed, efficiency, and scalability in addressing complex challenges. By harnessing the core principles of quantum mechanics, quantum computing enables AI to process vast datasets and solve problems that would take conventional systems centuries to complete.Despite these considerable advantages, this progress faces challenges related to system security and ethical considerations. Additionally, geopolitical competition could reshape global power dynamics. The research concludes with an optimistic vision for the future of Quantum AI, predicting remarkable advancements by the 2040s that could pave the way for a smarter, more efficient, and sustainable future for all.
Keywords: Quantum Computing; Artificial Intelligence; Deep Learning; Quantum Mechanics; Quantum AI; General Artificial Intelligence; Geopolitics; Innovation